2018
DOI: 10.12957/pr.2017.33370
|View full text |Cite
|
Sign up to set email alerts
|

Conto “Negrinha” à luz do letramento crítico: uma experiência sobre identidade no projeto Mais Educação

Abstract: O presente artigo é fruto de uma atividade pedagógica sobre o racismo por meio da leitura crítica e de atividades de compreensão e intervenção em um contexto escolar do projeto Mais Educação na cidade de Maricá, situada no Estado do Rio de Janeiro. Essa atividade foi elaborada em uma escola estadual em uma turma do ensino fundamental II, com o intuito de estimular a leitura crítica do texto literário Negrinha de Monteiro Lobato. A abordagem do estudo tem como fundamento teórico e metodológico as concepções de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Critical literacy research has also shown that linking a literary text to the students' context encourages the students to reflect on their reality and enhances their participation in critical literacy practices (Silva et al, 2017;Silva, 2020). Thus, creating memes that recontextualize a literary text and incorporate new texts that reveal student's critical consciousness might open opportunities for promoting critical literacy in the classroom.…”
Section: Memes As Multimodal Intertextual Participatory Resourcesmentioning
confidence: 99%
“…Critical literacy research has also shown that linking a literary text to the students' context encourages the students to reflect on their reality and enhances their participation in critical literacy practices (Silva et al, 2017;Silva, 2020). Thus, creating memes that recontextualize a literary text and incorporate new texts that reveal student's critical consciousness might open opportunities for promoting critical literacy in the classroom.…”
Section: Memes As Multimodal Intertextual Participatory Resourcesmentioning
confidence: 99%